Development of lymphocyte populations in the human foetal thymus and spleen - Hayward, A. R. (1974)
T and B lymphocytes in the human foetal thymus and spleen were studied to determine the distribution and degree of development which takes place before exposure to environmental antigens occurs. Tests applied were spontaneous and complement-dependent rosette formation and immunofluorescence to detect surface immunoglobulins. Most thymus lymphocytes were spontaneous rosette-forming cells: the percentage of these cells in the spleen was lower. Complement receptor lymphocytes (CRL) were found in the spleen but not the thymus, suggesting that these tissues contain lymphocytes of different origin. Lymphocytes with surface immuno-globulin (SIg lymphocytes) were more numerous in the spleen than the thymus. Analysis of class-specific heavy chain and light chain determinants suggests that some foetal B cells carry heavy chains of more than one class. A possible model for foetal B-cell development and its relationship to antigen drive is discussed.